Prediction of Hamstring Autograft sizes for Anterior Cruciate Ligament Reconstruction using Preoperative Magnetic Resonance Imaging - Shrestha, Prakash; Singh Thapa, Sunil; Mahara, Deepak Prakash; Paudel, Sharma; Lamichhane, Arjun; Saud, Tejendra (Journal of Nepal Health Research Council, 2023)
Background: The purpose of this study is to determine whether preoperative magnetic resonance image measurements can predict the hamstring tendon autograft diameter during anterior cruciate ligament reconstruction. Methods: We prospectively evaluated Forty-two patients with anterior cruciate ligament injury who underwent reconstruction using hamstring tendon autograft. Preoperative diameters and cross-sectional areas of the hamstring tendons were estimated using magnetic resonance imaging of the knee. Intraoperative diameters of the hamstring tendon graft were measured using a cylindrical graft sizer. We used Pearson’s correlation test to compare the Preoperative and intraoperative graft size measurements. A possible cutoff value for the hamstring graft size was determined using Receiver operating characteristic analysis. Results: The mean age of the patient in the study was 27.5 ± 8.5 years. There were statistically significant correlations between preoperative and intraoperative hamstring tendon graft measurements (P < 0.001). Our study found 13.3 mm² cross-sectional area as the cutoff for predicting 7mm of quadrupled hamstring graft size with both sensitivity and specificity of 85.7 %, respectively. Conclusions: We can conclude that preoperative magnetic resonance imaging measurements can predict the intraoperative graft size. This study can help in preoperatively planning for the graft choice. Keywords: Anterior cruciate ligament (ACL), Hamstring graft, Magnetic resonance imaging (MRI), Prediction